Fiscal Capacity Development for Enhancing Regional Autonomy in Indonesia’s Wetland Areas: A Strategic Model for Posthumanist Public Policy - Isyandi, B.; Ekwarso, Hendro; Hamidi, Wahyu (Journal of Posthumanism, 2025)
This study aims to identify a strategic model of fiscal capacity to enhance regional autonomy and economic resilience in wetland areas of Riau Province, Indonesia. Utilizing a mixed-method approach, the research explores how regional own-source revenues, intergovernmental transfers, and capital expenditure allocation impact local fiscal independence. The findings show that fiscal capacity is significantly constrained by central government dependency, underutilized local revenue instruments, and low capital investment. Only three out of twelve districts achieved substantial own-source revenue above IDR 300 billion, while others remain highly dependent on central transfers. The paper proposes a responsive fiscal model integrating both demand-side (increased consumption, investment, and exports) and supply-side (technological development and resource availability) strategies. The model holds potential for transforming wetlands into sustainable, autonomous economic zones aligned with posthumanist development principles.